2021
DOI: 10.3390/antiox10020277
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Stress and Reactive Oxygen Species: Generation, Signaling, and Defense Mechanisms

Abstract: Climate change is an invisible, silent killer with calamitous effects on living organisms. As the sessile organism, plants experience a diverse array of abiotic stresses during ontogenesis. The relentless climatic changes amplify the intensity and duration of stresses, making plants dwindle to survive. Plants convert 1–2% of consumed oxygen into reactive oxygen species (ROS), in particular, singlet oxygen (1O2), superoxide radical (O2•–), hydrogen peroxide (H2O2), hydroxyl radical (•OH), etc. as a byproduct of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
281
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 632 publications
(394 citation statements)
references
References 270 publications
8
281
1
1
Order By: Relevance
“…Reactive oxygen species produced in plants are composed of both free radicals and non-radicals [2,13]. The common cellular ROS radicals are O 2…”
Section: Types Of Reactive Oxygen Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive oxygen species produced in plants are composed of both free radicals and non-radicals [2,13]. The common cellular ROS radicals are O 2…”
Section: Types Of Reactive Oxygen Speciesmentioning
confidence: 99%
“…Due to disruption of the equilibrium between ROS production and antioxidant defense, oxidative stress occurs under abiotic stresses (including salinity). Non-enzymatic as well as enzymatic components of the antioxidant defense system scavenge or detoxify the excessive ROS which mitigates the negative effect of oxidative stress [2,13]. The most investigated major components of the antioxidant defense system are superoxide dismutase (SOD), peroxidase (POD/POX), catalase (CAT), the ascorbate-glutathione (AsA-GSH) cycle enzymes (ascorbate peroxidase, APX; monodehydroascorbate reductase, MDHAR; dehydroascorbate reductase, DHAR; glutathione reductase, GR), peroxiredoxins (PRX), glutathione peroxidases (GPX) and glutathione S-transferases (GST), which act in reducing ROS under abiotic stress including salt stress [2,14].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, ROS is scavenged by antioxidant enzymes. For example, SOD catalyzes O 2 - into H 2 O 2 , and then H 2 O 2 is disintegrated by CAT and APX [ 42 , 45 , 46 ]. Previous studies also reported that Mo supply relieved oxidative damage by improving the antioxidant defense ability of plants under cold, drought, salt stress, and heavy metals [ 11 , 13 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…99,100 Using such dimedone probes together with mass spectrometry has enabled identification of 226 sulfenylated proteins in H 2 O 2 -treated Arabidopsis cells 100 and 11 sulfenylated proteins in H 2 O 2 -stressed Arabidopsis seedlings. 101 While these probes could detect overall levels of SOH in plant cells, the identification of the site of modified cysteines became possible with the use of a more reactive SOH reactive probe, BTD (1-(pent-4-yn-1-yl)-1H-benzo[c] [1,2]thiazin-4(3H)one 2,2-dioxide) with a 'clickable' handle for biotinylation of labelled fragments (Fig. 4B).…”
Section: Protein Oxidation Productsmentioning
confidence: 99%